IMPROVING STUDENTS’ ABILITY IN WRITING A RECOUNT TEXT THROUGH CONTEXTUAL TEACHING AND LEARNING (CTL) AT CLASS X3 OF SMAN 12 PEKANBARU - Eliwarti, Zikri Eliwarti; Ras, Fahri Ras; ', Ahsanuz (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The objective of the study was to find out whether or not the Contextual Teaching and Learning (CTL) could improve the writing ability of first year students at SMAN 12 Pekanbaru in writing Recount Texts. The research was a classroom action research performing in only one cycle which consisted of five meetings. The subjects were 33 students X3. The data were collected from tests conducted before and after CTL  implemented (Pre-Test and Post-Tests), and supported by a set of observation sheets for the researcher and observation sheets for the students taken during the implementation of CTL in each meeting. That CTL could improve students’ ability in writing recount texts has been proven in the study. The students’ average scores had significantly increased from 49.53 in Pre-Test to 78.11 in Post-Test. The results of Post-Test showed that 29 students could reach the minimum passing grade for writing recount texts, and there were only 4 students didn’t pass the minimum passing grade (75). The success of the implementation of CTL was also supported by the data collected from observation sheets for the researcher and observation sheets for the students which found that students were being more active during the process of teaching and learning. As conclusion, the study had proven that CTL gave positive influences upon the development of students’ ability in writing English Texts, especially recount texts. Keywords: Contextual Teaching and Learning, students’ ability, writing recount texts.